Training and Implementation of Coastal Waste-Based Bioreeftek for Coral Reef Restoration in Wangel Village, Aru Islands - Louvenska N Latupeirissa; Siti Rahmawati Kahar; Prili Maria Sairdekut; Ribka Aprillia Selly; Karten Halirat; Muh Akbar Yanlua; Ricky Marthen Wattimena (Civiliza Publishing, 2026)
Coral reef degradation in the coastal areas of the Aru Islands due to overexploitation and coastal waste pollution has become an urgent environmental issue that requires innovative and participatory approaches. This community service activity was conducted from February to March 2026, with the peak activity on April 1, 2026, at Wangel Beach, Aru Islands Regency. The purpose of this activity was to enhance the knowledge and skills of coastal communities in coral reef restoration through training and the implementation of Bioreeftek techniques based on the utilization of coastal waste. The methods employed included a socialization program themed “Save the Reefs, Secure Aru’s Future,” online training on Bioreeftek media preparation, and direct practice in constructing and deploying the media in coastal waters. The activity involved approximately 50 participants, including coastal residents, youth groups, and local fishermen. The results indicated an improvement in community understanding and skills in processing coastal waste into environmentally friendly coral transplantation media. A total of four Bioreeftek units were successfully constructed and deployed in waters with potential as snorkeling tourism sites. This activity demonstrates that Bioreeftek is an effective innovation for coral reef restoration as well as a strategy for community empowerment. Therefore, this approach is important to be developed as a sustainable model for coastal ecosystem conservation.